Influence of Workshop Facility Toward Results Student Practice on Welding Engineering in SMK Kristen Getsemani Manado - Djamen, Arje Cerullo; Kapoh, Timothy Waraney; Manengkei, Steven Bons; Katuuk, Deitje Adolfien; Rotty, Viktory Nicodemus Joufree; Lengkong , Jeffry Sony Junus; Usoh, Elni Jeini (JR Education, 2022)
The purpose of this study was to determine the effect of workshop facilities on students' practicum results in Welding Engineering Subjects at the Getsemani Christian Vocational school, Manado. This research is included in correlational research. The number of respondents as many as 30 people. The instrument for collecting data from practicum results is a questionnaire. Data analysis uses correlational techniques to determine whether there is a significant relationship between the two variables using the product moment correlation methods. The result is that there is a significant influence on the completeness of workshop facilities on the results of student practice on Welding Engineering subjects at the Getsemani Christian Vocational School Manado